IMPLEMENTASI KEBIJAKAN UJIAN NASIONAL DI SEKOLAH MENENGAH PERTAMA KOTA SEMARANG (STUDI DI SMP AL FATTAH) - Pratama, Arief; Nurcahyanto, Herbasuki; Dwimawanti, Ida Hayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Education is one of the very important factor in a country. The quality of a good education can make that developed and developing countries. The quality of education can be a tool to measure the progress of the country, because education is an important actor in improving human resources. Regulation of the Minister of national education No. 75 of 2009 About National high school Exam First mention that the national examination (UN) is an activity measurement and assessment of competence of learners nationwide at the level of primary and secondary education. National examination aims to evaluate the competence of graduates nationwide on certain subjects in the subjects of science and technology. This research aims to analyze the implementation of policy and the factors that support the national exam and impede the implementation of the national examination in JUNIOR HIGH SCHOOL Al Fattah Semarang. This research is a qualitative dekskriptif research. Data done with by means of study kepustakaan, documentation and deep interview with several informer. This research also use the model implementation policy according to george edward iii, there are four factors a mutually terkai one another in mempenggaruhi success and failure implementation communication, namely resources, the disposition and structure bureaucracy. Can be concluded that implementation policy national examination in smp al fattah city semarang still find the storm. It can be seen from some of the issues found in honesty and responsibility still weak, the students ( students ) that still mencontek and room ujian still not optimal. Ditemukanya factor inhibitors as resources in this facility not optimal from school, so that it needs to be repaired.